Teaching teens with ADD and ADHD : a quick reference guide for teachers and parents - Zeigler Dendy, Chris A. 4 0 16; 5 (Bethesda, MD : Woodbine House, 2000)
Contains a comprehensive reference guide for teaching teens with ADD and ADHD and offers practical strategies, organizational tools and seventy-five summaries related to attention deficit disorders.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Education (Secondary);Education -- Attention-deficit-disordered youth;Attention-deficit hyperactivity disorder;Attention-deficit-disordered youth -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc; 20; 2